2018
DOI: 10.3390/universe4100098
|View full text |Cite
|
Sign up to set email alerts
|

The Vacuum State of Primordial Fluctuations in Hybrid Loop Quantum Cosmology

Abstract: We investigate the role played by the vacuum of the primordial fluctuations in hybrid Loop Quantum Cosmology. We consider scenarios where the inflaton potential is a mass term and the unperturbed quantum geometry is governed by the effective dynamics of Loop Quantum Cosmology. In this situation, the phenomenologically interesting solutions have a preinflationary regime where the kinetic energy of the inflaton dominates over the potential. For these kind of solutions, we show that the primordial power spectra d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 93 publications
1
23
0
Order By: Relevance
“…(Gupt and Singh, 2012;Gupt and Singh, 2013; and references therein.]. In particular, the last two approaches have been widely studied and found that they are all consistent with current cosmological observations (Agullo and Morris, 2015;de Blas and Olmedo, 2016;Castelló Gomar et al, 2017;Agullo et al, 2018;Elizaga Navascués et al, 2018;Navascues et al, 2018;Wu et al, 2018;Zhu et al, 2018). In addition, within the framework of the dressed metric approach recently it has been also shown that some anomalies from the CMB data (Akrami and Planck collaboration, 2020;Akrami and Planck collaboration, 2020;Schwarz et al, 2016) can be reconciled purely due to the quantum geometric effects (Ashtekar et al, 2020;Ashtekar et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
“…(Gupt and Singh, 2012;Gupt and Singh, 2013; and references therein.]. In particular, the last two approaches have been widely studied and found that they are all consistent with current cosmological observations (Agullo and Morris, 2015;de Blas and Olmedo, 2016;Castelló Gomar et al, 2017;Agullo et al, 2018;Elizaga Navascués et al, 2018;Navascues et al, 2018;Wu et al, 2018;Zhu et al, 2018). In addition, within the framework of the dressed metric approach recently it has been also shown that some anomalies from the CMB data (Akrami and Planck collaboration, 2020;Akrami and Planck collaboration, 2020;Schwarz et al, 2016) can be reconciled purely due to the quantum geometric effects (Ashtekar et al, 2020;Ashtekar et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
“…within the Hybrid Quantization Approach [32] in order to deal with (both scalar and fermionic) perturbations in quantum cosmology (see, for instance, Refs. [100][101][102][103][104][105][106][107]).…”
Section: Discussionmentioning
confidence: 99%
“…The final article I would like to discuss concerns a study of primordial fluctuations in a hybrid loop quantum cosmology (HLQC) model [15]. HLQC models are extensions of LQC where small anisotropies and inhomogeneities are included, in such a way that the dominant effects of quantum geometry are studied using the standard quantization of LQC.…”
mentioning
confidence: 99%
“…The opposite situation characterizes the slow-roll inflationary phase. The work of [15] shows explicitly that the primordial power spectrum depends strongly on the choice of vacuum. In general, the adiabatic spectra are suppressed at large scales, but exhibit rapid oscillations at intermediate scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation